The Effect of Resin and NH4OH Addition in The Making of Ammonium Silica Fertilizer from Geothermal Sludge - Wahyusi, Kindriari Nurma; Nandini, Atika; Utami, Lucky Indrati; Siswanto; Utami, Isni; Mardhiyah, Nurul; Nofita, Dian (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2021)
Geothermal sludge is a waste product from geothermal where it contains SiO2 which can be used as fertilizer. In this study, the making of silica ammonium fertilizer was carried out by taking salicy acid from geothermal sludge by extracting and adding resin which was then modified with NH4OH addition. Extraction was done using 1000 ml of KOH 1 N to dissolve 60 grams of Geothermal Sludge. Resins are added with variations in resin weight, namely, 5, 10, 20, 30, and 40 grams. NH4OH was added with variations in concentrations namely 3, 6, 9, 12 and 15% with a ratio of filtrate and NH4OH solution of 1: 1. The resulting ammonium silica inorganic liquid fertilizer products were analyzed for free silica and ammonia levels. The results of this study indicate that the levels of free silica and ammonia are influenced by the weight of the resin used and the concentration of ammonium hydroxide mixed. From the results of the research, it was found that inorganic silica liquid fertilizer with the highest SiO2 content in ammonium silica liquid fertilizer occurred when adding 20 grams of resin with the addition of NH4OH with a concentration of 15% which was 1,831.87 mg / L while the highest NH3 content in fertilizer liquid ammonium silica occurs when adding 40 grams of resin with the addition of NH4OH with a concentration of 15% which is equal to 252,312.80 mg / L.